2012
DOI: 10.1152/ajprenal.00021.2012
|View full text |Cite
|
Sign up to set email alerts
|

CD36 mediates proximal tubular binding and uptake of albumin and is upregulated in proteinuric nephropathies

Abstract: Baines RJ, Chana RS, Hall M, Febbraio M, Kennedy D, Brunskill NJ. CD36 mediates proximal tubular binding and uptake of albumin and is upregulated in proteinuric nephropathies. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 45 publications
(52 reference statements)
1
40
0
Order By: Relevance
“…For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35). The elevated level of serum/plasma/urinary Fabp4 is considered a predictor or biomarker for renal dysfunction in diabetes and cardiovascular diseases (23)(24)(25)(26)(27).…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35). The elevated level of serum/plasma/urinary Fabp4 is considered a predictor or biomarker for renal dysfunction in diabetes and cardiovascular diseases (23)(24)(25)(26)(27).…”
Section: Articlesmentioning
confidence: 99%
“…We observed that BSA-PA stimulated both CD36 and Fabp4 protein expression in a dose-dependent manner in IRPTCs. CD36 has been shown to mediate PTC apoptosis (36) and to influence the binding and uptake of albumin in PTCs to promote proteinuria (35). The activated CD36 in PTCs targets JNK, ROS, and inflammatory cytokines to facilitate renal dysfunction (22).…”
Section: Articlesmentioning
confidence: 99%
“…Current studies suggest a role for CD36 in mediating cardiovascular disease associated with type II diabetes, insulin resistance, and obesity in rodent models [16] and in hypertensive humans [17]. Human genetic studies also support a role for CD36 in dyslipidemia, obesity and metabolic diseases [18–20], and CD36 protein expression is increased in kidney proximal convoluted tubule cells (PCT) in patients with proteinuria [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The proximal tubule is known to endocytose a number of low-molecular-weight proteins, [3][4][5] and the molecular size of BTP is similar to light chains (w25,000 Da) that are filtered and metabolized by the kidney. 6 We agree that further investigations are needed to define renal handling of BTP; for example, determining whether proximal tubular cells uptake BTP in vitro 7,8 and additional measurements of BTP clearance in vivo using methods that do not rely on radioactive labels. 125 I in the urine suggests that the 125 I-labelled BTP is freely filtered and then 125 I is released from the BTP, presumably as BTP is metabolized."…”
Section: Interpreting the Evidencementioning
confidence: 93%